PERAN PERPUSTAKAAN SEKOLAH DALAM MENINGKATKAN MINAT BACA SISWA DI SDN PABIAN IV - Putri Wulandari; Maghfiratul Fitriyah; Mohammad Fajri; Nursaib Asra (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study uses a qualitative descriptive approach to explore the role of school libraries in enhancing students' reading desire and their interest in reading. With this approach, the researcher can explain and describe various aspects related to the contribution of school libraries in stimulating students' reading interest. Primary data is obtained directly from primary sources, while secondary data is collected from other relevant sources. The research findings reveal that the role of the school library successfully attracted students who were previously less interested in visiting the library, making them more enthusiastic and spending more time in the library, especially outside of class hours. This study also provides new insights for library staff on better management practices. One of the factors contributing to the low quality of learning is the lack of utilization of learning resources by teachers and students.